Landau problem on the ellipsoid, hyperboloid and paraboloid of revolution; Modern Physics Letters A; Vol. 29, iss. 29 - Gevorgyan E. Eva; Nersessian A. P. Armen Petrosovich; Ohanyan V. Vadim; Tolkachev E. Evgeny (2014, 2014)
Title screen